A critical afrocentric analysis of South Africa’s SADC-mandated mediation in Zimbabwe, 2007 – 2014 - Zondi, Siphamandla (University of Pretoria, 2023)
Thesis (PhD (International Relations))--University of Pretoria, 2022.